Method for preparing perovskite thin film by utilizing ultrasonic-assisted hot air desolvation and application
Through ultrasonic-assisted hot air desolution method, the problems of insecure anti-solvent use and difficulty in film crystallization control in the prior art are solved, and the preparation of high-quality perovskite films is realized, and the performance and stability of perovskite solar cells are improved. .
Patent Information
- Application Number
- CN202411177522.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-26
- Publication Date
- 2024-12-27
AI Technical Summary
The prior art often uses volatile toxic anti-solvents when preparing perovskite films, which leads to unsafe process and is difficult to regulate film crystallization, affecting the performance and stability of perovskite solar cells.
Perovskite films are prepared by ultrasonic-assisted hot air desolution method. By combining spin coating, ultrasonic treatment and hot air desolution, the crystallization nucleation and diffusion of the film are promoted, and the crystallization quality and stability of the film are improved.
The green and safe process without anti-solvents is realized, the crystallization quality and performance of perovskite films are improved, the defect density and internal stress are reduced, and the stability and photoelectric performance of perovskite solar cells are improved.
Smart Images

Figure CN119212521A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of perovskite solar cell manufacturing, and specifically relates to a method for preparing a perovskite film by utilizing ultrasound-assisted hot air desolventizing and an application thereof, in particular to an application in perovskite solar cells. Background Art
[0002] As an unlimited, clean, abundant and long-lasting energy source, solar energy is regarded as the key to solving energy crisis and environmental problems. In this regard, perovskite solar cells, as pioneers in the field of solar cells, play a vital role. As a cutting-edge technology in the photovoltaic industry, perovskite solar cells are particularly suitable for photovoltaic building integration with their advantages of abundant raw materials, low cost and high photoelectric conversion efficiency, meeting the large-scale development needs of green buildings.
[0003] To achieve high-performance and long-term stable perovskite solar cells, it is crucial to regulate the crystallization process of the perovskite film. An excellent perovskite film can not only improve the photoelectric conversion efficiency (PCE), but also reduce defects and improve stability. In the process of preparing perovskite films, the existing technology generally uses a solvent insoluble in perovskite as an anti-solvent to extract the solvent in the perovskite precursor. Common anti-solvents include toluene, ether, chlorobenzene, etc., which are all volatile toxic liquids. Therefore, for green and safety considerations, the process without anti-solvent is worth studying, but without anti-solvent, it is more difficult to regulate the crystallization of the film.
[0004] Based on the above reasons, this application is filed. Summary of the invention
[0005] Based on the above reasons, in view of the problems or defects existing in the prior art, the purpose of the present invention is to provide a method for preparing perovskite thin film using ultrasound-assisted hot air desolventization and its application in perovskite solar cells, so as to solve or at least partially solve the above technical defects existing in the prior art.
[0006] In order to achieve the above first object of the present invention, the technical solution adopted by the present invention is as follows:
[0007] A method for preparing a perovskite film by using ultrasound-assisted hot air desolventizing, the method specifically comprising the following steps:
[0008] The perovskite precursor solution is spin-coated, and then the obtained wet film is subjected to ultrasonic treatment, hot air desolvation treatment and annealing treatment in sequence; or the obtained wet film is subjected to ultrasonic treatment and hot air desolvation treatment at the same time, and finally annealing treatment is performed to obtain the perovskite film.
[0009] Furthermore, in the above technical solution, the concentration of the perovskite precursor solution is 1.0-3.0 mol / L.
[0010] Furthermore, in the above technical solution, the spin coating is to spin coat the perovskite precursor solution at a rotation speed of 2000-5000 rpm and an acceleration of 1000-2500 rpm / s.
[0011] Furthermore, in the above technical solution, the process parameters adopted for the ultrasonic treatment are as follows: ultrasonic frequency is 20-100Khz, ultrasonic time is 1-30s, and ultrasonic power is 10-100W.
[0012] Furthermore, in the above technical solution, the process parameters adopted by the hot air desolventizing treatment are as follows: hot air desolventizing temperature is 10-80°C, treatment time is 2-10s, and air flow rate is 300-1000L / min.
[0013] Preferably, in the above technical solution, the hot air treatment time is 5s.
[0014] Specifically, in the above technical solution, the gas blown by the hot wind is low-humidity air or low-humidity inert gas; the inert gas is any one of nitrogen, argon, etc.; the low humidity means that the gas humidity is below 20%.
[0015] Further, in the above technical solution, the material chemical formula of the perovskite film is ABX3, wherein A is FA + , M.A. + , Cs + , Rb + Any one or more of the following, B is Pb 2+ , Sn 2+ , X is I ﹣ , Cl ﹣ Br ﹣ Any one or more of the .
[0016] The second object of the present invention is to provide the use of the perovskite film prepared by the above method as a light absorbing layer in a perovskite solar cell.
[0017] The third object of the present invention is to provide a perovskite solar cell, the structure of which is composed of a transparent conductive substrate, an electron transport layer, a perovskite light absorbing layer, a hole transport layer and a back electrode stacked from bottom to top; wherein: the perovskite light absorbing layer is a perovskite film prepared by the above-mentioned method.
[0018] Furthermore, in the above technical solution, the conductive material on the surface of the substrate is one of ITO or FTO.
[0019] Further, in the above technical solution, the material of the electron transport layer is [6,6]-phenyl-C 61-Methyl butyrate (PC 61 BM), zinc oxide (ZnO), titanium dioxide (TiO2), and tin dioxide (SnO2) are any one or more thereof.
[0020] Furthermore, in the above technical solution, the material of the hole transport layer is any one or more of poly (3,4-ethylenedioxythiophene) / polystyrene sulfonate (PEDOT:PSS), poly (bis(4-phenyl)(2,4,6-trimethylphenyl)amine) (PTAA), and 2,2,7,7-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9-spirobifluorene (Spiro-OMeTAD).
[0021] Furthermore, in the above technical solution, the material of the back electrode is any one or more of Au, Ag, Cu, Al or low-temperature carbon electrode.
[0022] A fourth object of the present invention is to provide a method for preparing the above-mentioned perovskite solar cell, the method comprising the following steps:
[0023] (1) Substrate pretreatment: clean and dry the transparent conductive substrate for later use, referred to as the bottom electrode;
[0024] (2) Preparation of electron transport layer: After preparing the transport layer solution, stir it evenly, and then spin-coat it on the bottom electrode. After annealing, a thin film is obtained, which is referred to as the bottom electrode / electron transport layer;
[0025] (3) Preparing a perovskite light absorbing layer: the perovskite light absorbing layer is a perovskite film, and the perovskite film is prepared by the above-mentioned method of preparing a perovskite film by using ultrasonic assisted hot air desolvation;
[0026] (4) preparing a hole transport layer: spin coating a hole transport layer precursor solution on the surface of the bottom electrode / electron transport layer / perovskite light absorbing layer, and drying to obtain a bottom electrode / electron transport layer / perovskite layer / hole transport layer film;
[0027] (5) Preparation of back electrode: Depositing metal as metal electrode on the bottom electrode / electron transport layer / perovskite layer / hole transport layer by thermal evaporation to obtain the perovskite solar cell.
[0028] Furthermore, in the above technical solution, the spin coating in step (2) and step (4) is to spin coat the perovskite precursor solution at a rotation speed of 2000-5000 rpm and an acceleration of 1000-2500 rpm / s.
[0029] When preparing the perovskite active layer, ultrasound is applied after spin coating, hot air desolventizing is performed immediately after the ultrasound treatment, and finally thermal annealing is performed. The ultrasound treatment used in the present invention is to promote nucleation at the bottom interface, and at the same time, ultrasound produces a microflow effect, so that the crystal nuclei are evenly diffused in the film, the crystal quality of the perovskite film is improved, the defect density is greatly reduced, the performance is improved, and the uniform crystallization also reduces its internal stress, so that the stability of the final device is improved.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] (1) The process of preparing perovskite film without anti-solvent in the present invention makes its preparation process safe, green and environmentally friendly, and the anti-solvent method is not suitable for large-scale preparation, wastes a lot of raw materials and has low economic benefits. In contrast, hot air desolventization, the gas blown by the hot air (low humidity (humidity below 20%) air or inert gas such as nitrogen) is safe and environmentally friendly, can be applied to large-scale preparation, has a high reuse rate and high economic benefits, and the use of hot air can pre-crystallize and generate crystallization sites on the surface. During the annealing process, the growth of perovskite will be more orderly, which can improve the crystallization quality and improve the uniformity of the film.
[0032] (2) The application of the ultrasonic process of the present invention can promote nucleation and crystallization, as well as a more uniform distribution of crystal nuclei, thereby increasing the size of the perovskite film, reducing grain boundaries, reducing defects, and improving performance. At the same time, the internal stress of the perovskite film is reduced, and ultimately the stability of the perovskite solar cell is improved. In addition, the ultrasonic-assisted process used in the present invention, as a physical treatment method, has significant advantages in preparing perovskite films over a large area.
[0033] (3) The method for preparing perovskite film of the present invention requires the synergistic effect of ultrasonic-assisted hot air desolventizing. If only ultrasonic treatment is used without hot air desolventizing or other desolventizing methods, there will be two situations: First, if the solvent fails to evaporate, the crystallization of the obtained perovskite film will be loose; second, if the solvent can evaporate, the crystallization speed of the perovskite film will be too fast, and the grains will be difficult to grow, which will eventually lead to small grain size and increased defects, both of which are not conducive to the preparation of high-quality perovskite film.
[0034] (4) The present invention applies an ultrasonic process on the ITO / SnO2 / FAPbI3 substrate, which is simple, economical, environmentally friendly and has high energy utilization rate.
[0035] (5) The present invention provides a process for preparing a thin film by ultrasonic-assisted hot air desolventization, which has the characteristics of low price, superior performance, safety and environmental protection. In addition, the perovskite solar cell obtained by using the perovskite thin film prepared by ultrasonic-assisted hot air desolventization of the present invention also has excellent photoelectric performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] The purpose of the present invention is to prepare a perovskite film without using an anti-solvent process. In order to form a higher quality perovskite layer, ultrasound is applied to the wet film after spin coating, mainly by substrate ultrasound. At this time, the wet film has produced a part of the perovskite nuclei and most of the perovskite intermediate phase nuclei. Since no anti-solvent is added, there is a lot of solvent in the wet film at this time, so the total amount of its nuclei is small and unevenly distributed. At this time, applying ultrasound to transmit mechanical energy can promote heterogeneous nucleation at the bottom interface and increase the number of nucleations. At the same time, ultrasound will produce a microflow effect, which can accelerate the diffusion of the nuclei, so that the nuclei are more evenly distributed in the wet film, so that the crystal quality is improved after desolventizing and annealing, the defect density is greatly reduced, the performance is improved, and the uniform crystallization will also reduce its internal stress, so that the stability of the final device is improved.
[0037] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0038] Figure 1 It is a schematic diagram of the process of preparing perovskite film by using ultrasound-assisted hot air desolventization and a schematic diagram of the ultrasound mechanism of the present invention.
[0039] Figure 2 It is the XRD (X-ray diffraction test) diagram of the perovskite film prepared in Examples 1-5 of the present invention and Comparative Example 1.
[0040] Figure 3 It is a statistical box plot of the photoelectric performance of the perovskite solar cells prepared in Examples 1-5 of the present invention and Comparative Example 1.
[0041] Figure 4 Surface SEM images (scanning electron microscope) of the perovskite films prepared in Examples 1-5 of the present invention and Comparative Example 1.
[0042] Figure 5 Surface SEM images of the perovskite films prepared in Comparative Example 1 and Example 6.
[0043] Figure 6 3 and 6. DETAILED DESCRIPTION
[0044] The present invention is further described in detail below through implementation cases. This implementation case is implemented based on the technology of the present invention, and a detailed implementation method and specific operation process are now given to illustrate that the present invention is creative, but the protection scope of the present invention is not limited to the following implementation cases.
[0045] According to the information contained in this application, various changes can be easily made to the precise description of the present invention for those skilled in the art.It should be understood that the scope of the present invention is not limited to defined processes, properties or components, because these embodiments and other descriptions are only for illustrating specific aspects of the present invention.
[0046] In order to better understand the present invention but not to limit the scope of the present invention, all the numbers used in this application to express the amount, percentage, and other numerical values should be understood as modified by the word "about" in all cases. Therefore, unless otherwise specified, the numerical parameters listed in the specification are approximate values, which may be changed according to the different ideal properties attempted to be obtained. Each numerical parameter should at least be regarded as obtained based on the reported significant figures and by conventional rounding methods.
[0047] The equipment and raw materials used in the present invention can be purchased from the market or are commonly used in the art. The methods in the following embodiments are all conventional methods in the art unless otherwise specified.
[0048] Example 1
[0049] A method for preparing a perovskite solar cell according to the present embodiment comprises the following steps:
[0050] (1) ITO glass cleaning: ITO glass (1.5 cm*1.5 cm) was ultrasonically cleaned for 5-15 minutes using Hellmanex III detergent dilution, deionized water, and 95% ethanol solution to remove surface impurities and organic matter, and then dried using a nitrogen gun and stored for later use.
[0051] (2) Preparation of electron transport layer: The cleaned ITO glass was plasma treated for 5 minutes and then removed for use. 15wt% SnO2 aqueous dispersion was mixed with deionized water at a volume ratio of 1:5 and stirred evenly. The above solution was spin-coated on the treated ITO glass at a speed of 5000 rpm and an acceleration of 2500 rpm / s for 30 seconds, and then annealed on a hot plate at 150 degrees for 30 minutes before removal.
[0052] (3) Preparation of FAPbI3 perovskite layer: First, prepare 1.4 mol / mL of perovskite precursor: 0.42 mol MACl (methylamine hydrochloride), 1.4 mol FAI (formamidine hydroiodide) and 1.53 mol PbI2 (lead iodide) are dissolved in 1 ml of a mixed solvent consisting of DMF (N,N-dimethylformamide) and NMP (N-methylpyrrolidone) in a volume ratio of 10:1, and then fully shaken and reserved. The prepared ITO / SnO2 plasma is first treated for 5 minutes and then spin-coated in a nitrogen glove box. A single-step spin coating method is used. Take 32 μL of perovskite precursor solution and drop it on ITO / SnO2. Spin coat for 25 seconds at a rotation speed of 4500 rpm and an acceleration of 1500 rpm / s. At the 17th second, add 150 μL of chlorobenzene as an anti-solvent, and then immediately place it on a 120 degree hot stage for annealing.
[0053] (4) Preparation of the hole transport layer Preparation of Spiro-OMeTAD: First, prepare the Spiro-OMeTAD precursor solution, which contains 72.3 mg Spiro-OMeTAD, 17.5 μL Li-TFSI solution (520 mg Li-TFSI dissolved in 1 mL acetonitrile), 28.8 μL 4-tert-butylpyridine and 1 mL chlorobenzene, and shake for use. Take 50 μL of the above-prepared Spiro-OMeTAD solution, spin coat for 30 seconds at a speed of 4000 rpm and an acceleration of 1000 rpm / s, and finally obtain an ITO / SnO2 / FAPbI3 / Spiro-OMeTAD film. After spin coating, move it to a dry air environment and store it for 12-24 hours.
[0054] (5) Preparation of silver electrode: A 100 nm thick silver electrode was deposited on the ITO / SnO2 / FAPbI3 / Spiro-OMeTAD film by thermal evaporation. The first 20 nm was The deposition rate of 20-45nm is slowly increased to The deposition rate is then maintained The deposition rate.
[0055] Example 2
[0056] A method for preparing a perovskite solar cell according to the present embodiment comprises the following steps:
[0057] (1) ITO glass cleaning: ITO glass (1.5 cm*1.5 cm) was ultrasonically cleaned for 5-15 minutes using Hellmanex III detergent dilution, deionized water, and 95% ethanol solution to remove surface impurities and organic matter, and then dried using a nitrogen gun and stored for later use.
[0058] (2) Preparation of electron transport layer: The cleaned ITO glass was plasma treated for 5 minutes and then removed for use. 15wt% SnO2 aqueous dispersion was mixed with deionized water at a volume ratio of 1:5 and stirred evenly. The above solution was spin-coated on the treated ITO glass at a speed of 5000 rpm and an acceleration of 2500 rpm / s for 30 seconds, and then annealed on a hot plate at 150 degrees for 30 minutes before removal.
[0059] (3) Preparation of FAPbI3 perovskite layer: First, prepare 1.4 mol / mL of perovskite precursor: 0.42 mol MACl (methylamine hydrochloride), 1.4 mol FAI (formamidine hydroiodide) and 1.53 mol PbI2 (lead iodide) are dissolved in 1 ml of a mixed solvent consisting of DMF (N,N-dimethylformamide) and NMP (N-methylpyrrolidone) in a volume ratio of 10:1, and then fully shaken and reserved. The prepared ITO / SnO2 plasma is first treated for 5 minutes and then spin-coated in a nitrogen glove box. A single-step spin coating method is used. Take 32 microliters of perovskite precursor solution and drop it on ITO / SnO2. Spin coat for 10 seconds at a rotation speed of 4000 rpm and an acceleration of 3000 rpm / s. Then place the resulting ITO / SnO2 / FAPbI3 substrate on a 40Khz ultrasonic vibrator (60W) and ultrasonicate it at 60% power for 15 seconds. Then, immediately perform hot air desolvation. The hot air temperature (45 degrees) and the air flow rate are approximately 460-500L / min. After blowing for 5 seconds, immediately place it on a 120-degree hot stage for annealing.
[0060] (4) Preparation of the hole transport layer Preparation of Spiro-OMeTAD: First, prepare the Spiro-OMeTAD precursor solution, which contains 72.3 mg Spiro-OMeTAD, 17.5 μL Li-TFSI solution (520 mg Li-TFSI dissolved in 1 mL acetonitrile), 28.8 μL 4-tert-butylpyridine and 1 mL chlorobenzene, and shake for use. Take 50 μL of the above-prepared Spiro-OMeTAD solution, spin coat for 30 seconds at a speed of 4000 rpm and an acceleration of 1000 rpm / s, and finally obtain an ITO / SnO2 / FAPbI3 / Spiro-OMeTAD film. After spin coating, move it to a dry air environment and store it for 12-24 hours.
[0061] (5) Preparation of silver electrode: A 100 nm thick silver electrode was deposited on the ITO / SnO2 / FAPbI3 / Spiro-OMeTAD film by thermal evaporation. The first 20 nm was The deposition rate of 20-45nm is slowly increased to The deposition rate is then maintained The deposition rate.
[0062] Example 3
[0063] A method for preparing a perovskite solar cell according to the present embodiment comprises the following steps:
[0064] (1) ITO glass cleaning: ITO glass (1.5 cm*1.5 cm) was ultrasonically cleaned for 5-15 minutes using Hellmanex III detergent dilution, deionized water, and 95% ethanol solution to remove surface impurities and organic matter, and then dried using a nitrogen gun and stored for later use.
[0065] (2) Preparation of electron transport layer: The cleaned ITO glass was plasma treated for 5 minutes and then removed for use. 15wt% SnO2 aqueous dispersion was mixed with deionized water at a volume ratio of 1:5 and stirred evenly. The above solution was spin-coated on the treated ITO glass at a speed of 5000 rpm and an acceleration of 2500 rpm / s for 30 seconds, and then annealed on a hot plate at 150 degrees for 30 minutes before removal.
[0066] (3) Preparation of FAPbI3 perovskite layer: First, prepare 1.4 mol / mL of perovskite precursor: 0.42 mol MACl (methylamine hydrochloride), 1.4 mol FAI (formamidine hydroiodide) and 1.53 mol PbI2 (lead iodide) are dissolved in 1 ml of a mixed solvent consisting of DMF (N,N-dimethylformamide) and NMP (N-methylpyrrolidone) in a volume ratio of 10:1, and then fully shaken and reserved. The prepared ITO / SnO2 plasma is first treated for 5 minutes and then spin-coated in a nitrogen glove box. A single-step spin coating method is used. Take 32 microliters of perovskite precursor solution and drop it on ITO / SnO2. Spin coat for 10 seconds at a rotation speed of 4000 rpm and an acceleration of 3000 rpm / s. Then place the resulting ITO / SnO2 / FAPbI3 substrate on a 40Khz ultrasonic vibrator (60W) and ultrasonicate at 60% power for 5 seconds. Then immediately perform hot air desolventizing. The hot air temperature (45 degrees) and the air flow rate are approximately 460-500L / min. After blowing for 5 seconds, immediately place it on a 120-degree hot stage for annealing.
[0067] (4) Preparation of the hole transport layer Preparation of Spiro-OMeTAD: First, prepare the Spiro-OMeTAD precursor solution, which contains 72.3 mg Spiro-OMeTAD, 17.5 μL Li-TFSI solution (520 mg Li-TFSI dissolved in 1 mL acetonitrile), 28.8 μL 4-tert-butylpyridine and 1 mL chlorobenzene, and shake for use. Take 50 μL of the above-prepared Spiro-OMeTAD solution, spin coat for 30 seconds at a speed of 4000 rpm and an acceleration of 1000 rpm / s, and finally obtain an ITO / SnO2 / FAPbI3 / Spiro-OMeTAD film. After spin coating, move it to a dry air environment and store it for 12-24 hours.
[0068] (5) Preparation of silver electrode: A 100 nm thick silver electrode was deposited on the ITO / SnO2 / FAPbI3 / Spiro-OMeTAD film by thermal evaporation. The first 20 nm was The deposition rate of 20-45nm is slowly increased to The deposition rate is then maintained The deposition rate.
[0069] Example 4
[0070] A method for preparing a perovskite solar cell according to the present embodiment comprises the following steps:
[0071] (1) ITO glass cleaning: ITO glass (1.5 cm*1.5 cm) was ultrasonically cleaned for 5-15 minutes using Hellmanex III detergent dilution, deionized water, and 95% ethanol solution to remove surface impurities and organic matter, and then dried using a nitrogen gun and stored for later use.
[0072] (2) Preparation of electron transport layer: The cleaned ITO glass was plasma treated for 5 minutes and then removed for use. 15wt% SnO2 aqueous dispersion was mixed with deionized water at a volume ratio of 1:5 and stirred evenly. The above solution was spin-coated on the treated ITO glass at a speed of 5000 rpm and an acceleration of 2500 rpm / s for 30 seconds, and then annealed on a hot plate at 150 degrees for 30 minutes before removal.
[0073] (3) Preparation of FAPbI3 perovskite layer: First, prepare 1.4 mol / mL of perovskite precursor: 0.42 mol MACl (methylamine hydrochloride), 1.4 mol FAI (formamidine hydroiodide) and 1.53 mol PbI2 (lead iodide) are dissolved in 1 ml of a mixed solvent consisting of DMF (N,N-dimethylformamide) and NMP (N-methylpyrrolidone) in a volume ratio of 10:1, and then fully shaken and reserved. The prepared ITO / SnO2 plasma is first treated for 5 minutes and then spin-coated in a nitrogen glove box. A single-step spin coating method is used. Take 32 microliters of perovskite precursor solution and drop it on ITO / SnO2. Spin coat for 10 seconds at a rotation speed of 4000 rpm and an acceleration of 3000 rpm / s. Then place the resulting ITO / SnO2 / FAPbI3 substrate on a 40Khz ultrasonic vibrator (60W) and ultrasonicate at 20% power for 15 seconds. Then, perform hot air desolvation immediately. The hot air temperature (45 degrees) and the air flow rate are approximately 460-500L / min. After blowing for 5 seconds, place it immediately on a 120-degree hot stage for annealing. (4) Preparation of the hole transport layer Preparation of Spiro-OMeTAD: First, prepare the Spiro-OMeTAD precursor solution, which contains 72.3 mg Spiro-OMeTAD, 17.5 μL Li-TFSI solution (520 mg Li-TFSI dissolved in 1 mL acetonitrile), 28.8 μL 4-tert-butylpyridine and 1 mL chlorobenzene, and shake for use. Take 50 μL of the above-prepared Spiro-OMeTAD solution, spin coat for 30 seconds at a speed of 4000 rpm and an acceleration of 1000 rpm / s, and finally obtain an ITO / SnO2 / FAPbI3 / Spiro-OMeTAD film. After spin coating, move it to a dry air environment and store it for 12-24 hours.
[0074] (5) Preparation of silver electrode: A 100 nm thick silver electrode was deposited on the ITO / SnO2 / FAPbI3 / Spiro-OMeTAD film by thermal evaporation. The first 20 nm was The deposition rate of 20-45nm is slowly increased to The deposition rate is then maintained The deposition rate.
[0075] Example 5
[0076] A method for preparing a perovskite solar cell according to the present embodiment comprises the following steps:
[0077] (1) ITO glass cleaning: ITO glass (1.5 cm*1.5 cm) was ultrasonically cleaned for 5-15 minutes using Hellmanex III detergent dilution, deionized water, and 95% ethanol solution to remove surface impurities and organic matter, and then dried using a nitrogen gun and stored for later use.
[0078] (2) Preparation of electron transport layer: The cleaned ITO glass was plasma treated for 5 minutes and then removed for use. 15wt% SnO2 aqueous dispersion was mixed with deionized water at a volume ratio of 1:5 and stirred evenly. The above solution was spin-coated on the treated ITO glass at a speed of 5000 rpm and an acceleration of 2500 rpm / s for 30 seconds, and then annealed on a hot plate at 150 degrees for 30 minutes before removal.
[0079] (3) Preparation of FAPbI3 perovskite layer: First, prepare 1.4 mol / mL of perovskite precursor: 0.42 mol MACl (methylamine hydrochloride), 1.4 mol FAI (formamidine hydroiodide) and 1.53 mol PbI2 (lead iodide) are dissolved in 1 ml of a mixed solvent consisting of DMF (N,N-dimethylformamide) and NMP (N-methylpyrrolidone) in a volume ratio of 10:1, and then fully shaken and reserved. The prepared ITO / SnO2 plasma is first treated for 5 minutes and then spin-coated in a nitrogen glove box. A single-step spin coating method is used. Take 32 microliters of perovskite precursor solution and drop it on ITO / SnO2. Spin coat for 10 seconds at a rotation speed of 4000 rpm and an acceleration of 3000 rpm / s. Then place the resulting ITO / SnO2 / FAPbI3 substrate on a 20Khz ultrasonic vibrator (60W) and ultrasonicate at 60% power for 15 seconds. Then, perform hot air desolvation immediately. The hot air temperature (45 degrees) and the air flow rate are approximately 460-500L / min. After blowing for 5 seconds, place it immediately on a 120-degree hot stage for annealing. (4) Preparation of the hole transport layer Preparation of Spiro-OMeTAD: First, prepare the Spiro-OMeTAD precursor solution, which contains 72.3 mg Spiro-OMeTAD, 17.5 μL Li-TFSI solution (520 mg Li-TFSI dissolved in 1 mL acetonitrile), 28.8 μL 4-tert-butylpyridine and 1 mL chlorobenzene, and shake for use. Take 50 μL of the above-prepared Spiro-OMeTAD solution, spin coat for 30 seconds at a speed of 4000 rpm and an acceleration of 1000 rpm / s, and finally obtain an ITO / SnO2 / FAPbI3 / Spiro-OMeTAD film. After spin coating, move it to a dry air environment and store it for 12-24 hours.
[0080] (5) Preparation of silver electrode: A 100 nm thick silver electrode was deposited on the ITO / SnO2 / FAPbI3 / Spiro-OMeTAD film by thermal evaporation. The first 20 nm was The deposition rate of 20-45nm is slowly increased to The deposition rate is then maintained The deposition rate.
[0081] Example 6
[0082] A method for preparing a perovskite solar cell according to the present embodiment comprises the following steps:
[0083] (1) ITO glass cleaning: ITO glass (1.5 cm*1.5 cm) was ultrasonically cleaned for 5-15 minutes using Hellmanex III detergent dilution, deionized water, and 95% ethanol solution to remove surface impurities and organic matter, and then dried using a nitrogen gun and stored for later use.
[0084] (2) Preparation of electron transport layer: The cleaned ITO glass was plasma treated for 5 minutes and then removed for use. 15wt% SnO2 aqueous dispersion was mixed with deionized water at a volume ratio of 1:5 and stirred evenly. The above solution was spin-coated on the treated ITO glass at a speed of 5000 rpm and an acceleration of 2500 rpm / s for 30 seconds, and then annealed on a hot plate at 150 degrees for 30 minutes before removal.
[0085] (3) Preparation of FAPbI3 perovskite layer: First, prepare 1.4 mol / mL of perovskite precursor: 0.42 mol MACl (methylamine hydrochloride), 1.4 mol FAI (formamidine hydroiodide) and 1.53 mol PbI2 (lead iodide) are dissolved in 1 ml of a mixed solvent consisting of DMF (N,N-dimethylformamide) and NMP (N-methylpyrrolidone) in a volume ratio of 10:1, and then fully shaken and reserved. The prepared ITO / SnO2 plasma is first treated for 5 minutes and then spin-coated in a nitrogen glove box. A single-step spin coating method is used. Take 32 microliters of perovskite precursor solution and drop it on ITO / SnO2. Spin coat for 10 seconds at a rotation speed of 4000 rpm and an acceleration of 3000 rpm / s. Then place the resulting ITO / SnO2 / FAPbI3 substrate on a 40Khz ultrasonic vibrator (60W) and perform ultrasound at 60% power while using hot air temperature (45 degrees) with an air flow rate of approximately 460-500L / min. After blowing for 5 seconds, immediately place it on a 120-degree hot stage for annealing.
[0086] (4) Preparation of the hole transport layer Preparation of Spiro-OMeTAD: First, prepare the Spiro-OMeTAD precursor solution, which contains 72.3 mg Spiro-OMeTAD, 17.5 μL Li-TFSI solution (520 mg Li-TFSI dissolved in 1 mL acetonitrile), 28.8 μL 4-tert-butylpyridine and 1 mL chlorobenzene, and shake for use. Take 50 μL of the above-prepared Spiro-OMeTAD solution, spin coat for 30 seconds at a speed of 4000 rpm and an acceleration of 1000 rpm / s, and finally obtain an ITO / SnO2 / FAPbI3 / Spiro-OMeTAD film. After spin coating, move it to a dry air environment and store it for 12-24 hours.
[0087] (5) Preparation of silver electrode: A 100 nm thick silver electrode was deposited on the ITO / SnO2 / FAPbI3 / Spiro-OMeTAD film by thermal evaporation. The first 20 nm was The deposition rate of 20-45nm is slowly increased to The deposition rate is then maintained The deposition rate.
[0088] Comparative Example 1
[0089] A method for preparing a perovskite solar cell in this comparative example comprises the following steps:
[0090] (1) ITO glass cleaning: ITO glass (1.5 cm*1.5 cm) was ultrasonically cleaned for 5-15 minutes using Hellmanex III detergent dilution, deionized water, and 95% ethanol solution to remove surface impurities and organic matter, and then dried using a nitrogen gun and stored for later use.
[0091] (2) Preparation of electron transport layer: The cleaned ITO glass was plasma treated for 5 minutes and then removed for use. 15wt% SnO2 aqueous dispersion was mixed with deionized water at a volume ratio of 1:5 and stirred evenly. The above solution was spin-coated on the treated ITO glass at a speed of 5000 rpm and an acceleration of 2500 rpm / s for 30 seconds, and then annealed on a hot plate at 150 degrees for 30 minutes before removal.
[0092] (3) Preparation of FAPbI3 perovskite layer: First, prepare 1.4 mol / mL of perovskite precursor: 0.42 mol MACl (methylamine hydrochloride), 1.4 mol FAI (formamidine hydroiodide) and 1.53 mol PbI2 (lead iodide) are dissolved in 1 ml of a mixed solvent consisting of DMF (N,N-dimethylformamide) and NMP (N-methylpyrrolidone) in a volume ratio of 10:1, and then fully shaken and reserved. The prepared ITO / SnO2 plasma is first treated for 5 minutes and then spin-coated in a nitrogen glove box. A single-step spin coating method is used. Take 32 microliters of perovskite precursor solution and drop it on ITO / SnO2. Spin coat for 10 seconds at a rotation speed of 4000 rpm and an acceleration of 3000 rpm / s. The hot air temperature is 45 degrees and the air flow rate is approximately 460-500 L / min. After blowing for 5 seconds, immediately place it on a 120-degree hot stage for annealing.
[0093] (4) Preparation of the hole transport layer Preparation of Spiro-OMeTAD: First, prepare the Spiro-OMeTAD precursor solution, which contains 72.3 mg Spiro-OMeTAD, 17.5 μL Li-TFSI solution (520 mg Li-TFSI dissolved in 1 mL acetonitrile), 28.8 μL 4-tert-butylpyridine and 1 mL chlorobenzene, and shake for use. Take 50 μL of the above-prepared Spiro-OMeTAD solution, spin coat for 30 seconds at a speed of 4000 rpm and an acceleration of 1000 rpm / s, and finally obtain an ITO / SnO2 / FAPbI3 / Spiro-OMeTAD film. After spin coating, move it to a dry air environment and store it for 12-24 hours.
[0094] (5) Preparation of silver electrode: A 100 nm thick silver electrode was deposited on the ITO / SnO2 / FAPbI3 / Spiro-OMeTAD film by thermal evaporation. The first 20 nm was The deposition rate of 20-45nm is slowly increased to The deposition rate is then maintained The deposition rate.
[0095] Comparative Example 2
[0096] A method for preparing a perovskite solar cell in this comparative example comprises the following steps:
[0097] (1) ITO glass cleaning: The ITO glass was ultrasonically cleaned for 5-15 minutes using Hellmanex III detergent dilution, deionized water, and 95% ethanol solution to remove surface impurities and organic matter. It was then blown dry with a nitrogen gun and stored for later use.
[0098] (2 Preparation of electron transport layer: The cleaned ITO glass was plasma treated for 5 minutes and then taken out for use. 15wt% SnO2 aqueous dispersion was mixed with deionized water in a volume ratio of 1:5 and stirred evenly. The above solution was spin-coated on the treated ITO glass at a speed of 5000rpm and an acceleration of 2500rpm / s for 30s, and then annealed on a hot plate at 150 degrees for 30 minutes before being removed.
[0099] (3) Preparation of FAPbI3 perovskite layer: First, prepare 1.4 mol / mL of perovskite precursor (0.42 mol MACl, 1.4 mol FAI and 1.53 mol PbI2 dissolved in 1 ml of DMF: NMP = 10:1 mixed solution) and oscillate thoroughly before use. First, treat the prepared ITO / SnO2 plasma for 5 min, and then spin coat it in a nitrogen glove box. Use a single-step spin coating method. Take 32 microliters of the perovskite precursor solution and drop it on ITO / SnO2. Spin coat for 10 s at a speed of 4000 rpm and an acceleration of 3000 rpm / s. Use a hot air temperature (45 degrees) and an air flow rate of approximately 460-500 L / min. After blowing for 15 seconds, immediately place it on a 120-degree hot plate for annealing.
[0100] (4) Preparation of the hole transport layer Preparation of Spiro-OMeTAD: First, prepare the Spiro-OMeTAD precursor solution, which contains 72.3 mg Spiro-OMeTAD, 17.5 μL Li-TFSI solution (520 mg Li-TFSI dissolved in 1 mL acetonitrile), 28.8 μL 4-tert-butylpyridine and 1 mL chlorobenzene, and shake for use. Take 50 μL of the above-prepared Spiro-OMeTAD solution, spin coat for 30 seconds at a speed of 4000 rpm and an acceleration of 1000 rpm / s, and finally obtain an ITO / SnO2 / FAPbI3 / Spiro-OMeTAD film. After spin coating, move it to a dry air environment and store it for 12-24 hours.
[0101] (5) Preparation of silver electrode: A 100 nm thick silver electrode was deposited on the ITO / SnO2 / FAPbI3 / Spiro-OMeTAD film by thermal evaporation. The first 20 nm was The deposition rate of 20-45nm is slowly increased to The deposition rate is then maintained The deposition rate.
[0102] Figure 1 The figure is a schematic diagram of the process of preparing perovskite film by ultrasonic-assisted hot air desolventization and a schematic diagram of the ultrasonic mechanism of the present invention. Figure 1 As shown in (a), the perovskite wet film has just been spin-coated. At this time, most of the solvent inside the wet film has not been dried out. In addition, since the surface is in contact with the air, the surface is more affected during the spin coating process, so the surface is more easily oversaturated, thus generating crystal nuclei. Therefore, there are more crystal nuclei on the surface than inside. Therefore, ultrasonic operation is performed next, as shown in FIG. Figure 1 As shown in (b), after ultrasound is applied to the bottom, the nuclei at the bottom interface absorb more energy to meet the free energy required for nucleation, so the nuclei begin to grow larger and more numerous. At the same time, ultrasound will produce a microflow effect inside the wet film, and the crystal nuclei inside begin to become uniform and orderly, as shown in Figure 1 (c) As shown. Finally, a hot air gun is used to remove the solvent and blow dry the internal solvent. The temperature brought by the hot air will cause the crystal nucleus to grow, promote the formation of nucleation sites on the surface, and produce uniform nuclei to start growing. According to the Ostwald ripening theory, the small nuclei continue to accept new deposited atoms and merge with other small pieces to slowly grow into uniform island crystals, as shown in Figure 1 As shown in (d), it is finally placed on a hot stage for annealing. Figure 2 It is the XRD (X-ray diffraction test) diagram of the perovskite film prepared by Examples 1-5 of the present invention and Comparative Example 1. After comparison, it can be found that because no ultrasound is applied, the crystallinity of Comparative Example 1 is the worst. By comparing Example 1 and Example 2, it can be found that the best ultrasonically treated sample and the anti-solvent sample are not much different. Compared with Example 2, Example 3 can be found that ultrasound 5s is significantly worse than ultrasound 15s. By comparing the XRD diagram, it can be found that its highest peak intensity is less than that of Example 2, and the half-slit width is also wider. Example 4 performs ultrasound at a power of 20%, and the power is too small and it is also found that the effect is obviously worse than that of Example 2. Example 5 performs ultrasound at a frequency of 20kHz. Compared with Example 2, it can be found that the crystallization is insufficient. The devices are all operated at room temperature and 100mW / cm 2 Under the irradiation of simulated solar light source, the photoelectric conversion efficiency (the efficiency of incident solar energy being converted into electrical energy), open circuit voltage (the output voltage of the solar cell under open circuit conditions), short circuit current (the current generated per unit area of the solar cell under short circuit condition) and fill factor (the ratio of the actual maximum power output of the solar cell to the theoretical maximum power output) are obtained. Figure 3It is a statistical box plot of the photoelectric performance of the perovskite solar cells prepared in Examples 1-5 of the present invention and Comparative Example 1. It is clearly found that due to the lack of ultrasound, Comparative Example 1 has the worst efficiency, with an average PCE of only 15.6%. At the same time, the worst repeatability, the lowest FF (fill factor), with an average FF of only 71%, and many surface internal defects; by comparing Example 1 and Example 2, it can be found that the performance of the best ultrasonic sample (average PCE of about 20.2%) and the anti-solvent sample (average PCE of about 20.0%) are already comparable. It can be found that the voltage of the solar cell prepared in Example 2 after ultrasonic treatment (average opening voltage of 1.1V) is significantly better than the voltage of the solar cell prepared in Anti-solvent Example 1 (average opening voltage of 1.07V). It is speculated that the ultrasonic sample has a certain modification effect on the bottom interface, but the current (the solar cell sample prepared by ultrasound in Example 2 is about 22.9mA / cm 2 The current of the solar cell prepared by the anti-solvent in Example 1 is 23.1 mA / cm 2 ) and FF (FF of solar cell prepared by ultrasound in Example 2 is about 80%, and FF of solar cell antisolvent prepared by antisolvent in Example 1 is 81%) are reduced, presumably because the crystal quality and defects restrict the improvement of these two parameters. Compared with Comparative Example 1, Examples 3, 4, and 5 are all improved, and the effect of ultrasonic assistance can be clearly found, among which the effect of ultrasonic time is more obvious. Figure 4 The surface SEM images (scanning electron microscope) of the perovskite films prepared in Examples 1-5 and Comparative Example 1 of the present invention clearly show that Figure 4 As shown in (a), due to the absence of ultrasonic treatment, the surface crystallization is the worst, the grains are small, and there are many surface defects. At the same time, it can be found that Example 1 and Example 2 are respectively as Figure 4 (f) (e), as shown, it can be found that the optimal ultrasonic sample (Example 2) and the anti-solvent sample (Example 1) are not much different, and compared with Comparative Example 1, it can be found that the increase in the crystal size is still particularly obvious. Figure 4 (b), (c), and (d), it can be found that the grain size has increased, but it is worse than that of Examples 1 and 2. It can be found that the influence of ultrasonic time is relatively large, while the influence of frequency and power is not much different. It is speculated that the microflow effect takes time to advance. Figure 5 The surface SEM images of the perovskite films prepared in Comparative Example 1 and Example 6 show that the film surface is rough after blowing for 15 seconds, the grain boundaries are significantly widened, and voids appear. Blowing for 5 seconds is the best choice. Figure 6 This is the XRD diagram of the perovskite film prepared in Example 3 and Example 6. It can be found that the effect of simultaneous ultrasound and blowing is not obvious. It is speculated that the effect of ultrasound needs time to advance.
Claims
1. A method for preparing perovskite thin film by using ultrasonic assisted hot air desolventizing, characterized in that: The method specifically comprises the following steps: The perovskite precursor solution is spin-coated, and then the obtained wet film is subjected to ultrasonic treatment, hot air desolvation treatment and annealing treatment in sequence; or the obtained wet film is subjected to ultrasonic treatment and hot air desolvation treatment at the same time, and finally annealing treatment is performed to obtain the perovskite film.
2. The method according to claim 1, characterized in that: The concentration of the perovskite precursor solution is 1.0-3.0 mol / L.
3. The method according to claim 1, characterized in that: The spin coating is to spin coat the perovskite precursor solution at a rotation speed of 2000-5000 rpm and an acceleration of 1000-2500 rpm / s.
4. The method according to claim 1, characterized in that: The process parameters adopted for the ultrasonic treatment are as follows: ultrasonic frequency is 20-100Khz, ultrasonic time is 1-30s, and ultrasonic power is 10-100W.
5. The method according to claim 1, characterized in that: The process parameters adopted by the hot air desolventizing treatment are as follows: hot air desolventizing temperature is 10-80°C, treatment time is 2-10s, and air flow rate is 300-1000L / min.
6. The method according to claim 1, characterized in that: The material chemical formula of the perovskite film is ABX3, where A is FA + , M.A. + , Cs + , Rb + Any one or more of the following, B is Pb 2+ , Sn 2+ , X is I ﹣ , Cl ﹣ Br ﹣ Any one or more of the .
7. Use of the perovskite film prepared by the method according to any one of claims 1 to 6 as a light absorbing layer in a perovskite solar cell.
8. A perovskite solar cell, wherein the structure of the perovskite solar cell is composed of a transparent conductive substrate, an electron transport layer, a perovskite light absorption layer, a hole transport layer and a back electrode stacked from bottom to top; characterized in that: The perovskite light-absorbing layer is a perovskite film prepared by the method according to any one of claims 1 to 6.
9. The method for preparing a perovskite solar cell according to claim 8, characterized in that: The method comprises the following steps: (1) Substrate pretreatment: clean and dry the transparent conductive substrate for later use, referred to as the bottom electrode; (2) Preparation of electron transport layer: After preparing the transport layer solution, stir it evenly, and then spin-coat it on the bottom electrode. After annealing, a thin film is obtained, which is referred to as the bottom electrode / electron transport layer; (3) Preparing a perovskite light absorbing layer: the perovskite light absorbing layer is a perovskite film, and the perovskite film is prepared by the method for preparing a perovskite film by using ultrasonic-assisted hot air desolventization as described in any one of claims 1 to 6; (4) preparing a hole transport layer: spin coating a hole transport layer precursor solution on the surface of the bottom electrode / electron transport layer / perovskite light absorbing layer, and drying to obtain a bottom electrode / electron transport layer / perovskite layer / hole transport layer thin film; (5) Preparation of back electrode: Depositing metal as metal electrode on the bottom electrode / electron transport layer / perovskite layer / hole transport layer by thermal evaporation to obtain the perovskite solar cell.
10. The preparation method according to claim 9, characterized in that: The spin coating in step (2) and step (4) is to spin coat the perovskite precursor solution at a rotation speed of 2000-5000 rpm and an acceleration of 1000-2500 rpm / s.
